IL‐10 promotes endothelial progenitor cell infiltration and wound healing via STAT3. Issue 7 (7th June 2022) - Short, Walker D.; Steen, Emily; Kaul, Aditya; Wang, Xinyi; Olutoye, Oluyinka O.; Vangapandu, Hima V.; Templeman, Natalie; Blum, Alexander J.; Moles, Chad M.; Narmoneva, Daria A.; Crombleholme, Timothy M.; Butte, Manish J.; et al.
Abstract: Endothelial progenitor cells (EPCs) contribute to de novo angiogenesis, tissue regeneration, and remodeling. Interleukin 10 (IL‐10), an anti‐inflammatory cytokine that primarily signals via STAT3, has been shown to drive EPC recruitment to injured tissues. Our previous work demonstrated that overexpression of IL‐10 in dermal wounds promotes regenerative tissue repair via STAT3‐dependent regulation of fibroblast‐specific hyaluronan synthesis. However, IL‐10's role and specific mode of action on EPC recruitment, particularly in dermal wound healing and neovascularization in both normal and diabetic wounds, remain to be defined. Therefore, inducible skin‐specific STAT3 knockdown mice were studied to determine IL‐10's impact on EPCs, dermal wound neovascularization and healing, and whether it is STAT3‐dependent. We show that IL‐10 overexpression significantly elevated EPC counts in the granulating wound bed, which was associated with robust capillary lumen density and enhanced re‐epithelialization of both control and diabetic (db/db) wounds at day 7. We noted increased VEGF and high C‐X‐C motif chemokine 12 (CXCL12) levels in wounds and a favorable CXCL12 gradient at day 3 that may support EPC mobilization and infiltration from bone marrow to wounds, an effect that was abrogated in STAT3 knockdown wounds. These findings were supported in vitro. IL‐10 promoted VEGF and CXCL12 synthesis in primary murine dermal fibroblasts, with blunted VEGF expression upon blocking CXCL12 in the media by antibody binding. IL‐10‐conditioned fibroblast media also significantly promoted endothelial sprouting and network formation. In conclusion, these studies demonstrate that overexpression of IL‐10 in dermal wounds recruits EPCs and leads to increased vascular structures and faster re‐epithelialization.